Scalable production of bio-calcium oxide via thermal decomposition of solid - hatchery waste in a laboratory-scale rotary kiln - Suwanan Chuakham; Ajchara I. Putkham; Yuwadee Chaiyachet; Arnusorn Saengprajak; Kriangsak Banlue; Nipon Tanpaiboonkul; Apipong Putkham (Scientific Reports)
Abstract Chicken eggshell waste is an alternative renewable source for quicklime production. Eggshell waste has received significant attention from researchers due to it being a potential source of bio-CaO, which not only drives the circular economy concept but also supports sustainable development. However, experiments on the production of bio-CaO are normally conducted in a small lab-scale furnace. Furthermore, the eggshell raw material is collected from canteens or households, which is not suitable for economical or industrial production. Therefore, this study investigated the factors affecting the bio-CaO production from hatchery waste via both batch and continuous calcination process in a laboratory-scale rotary kiln for the first time. The eggshells were first separated from the solid hatchery waste. Then, the effect of preparation methods of raw eggshells on the properties of bio-CaO was investigated, including eggshells with and without membrane separation, various particle sizes, and with an increase of the percent raw material filling in the kiln from 5 to 20%. Calcination of the samples was performed in a rotary kiln at 800 °C with a 0.5 RPM rotating speed and a 5° inclination of the kiln. The effects of the calcination process in either an air or N2 atmosphere on the calcined product were also observed. Instrumental analysis shows that the production yield and purity of bio-CaO were in the range of 49–56 wt% and 97–98%, respectively. The results also indicated that the production yield of bio-CaO decreased to 17.7% with a decrease in the raw material particle size from 3.3 mm to 250 μm. Moreover, the production of bio-CaO with eggshells containing eggshell membrane decreases the purity of calcium oxide by about 0.7–1.0%. In addition, further increasing the filling volume of the kiln from 5 to 20% had only a slight effect on the purity and yield of the product. These results imply that it is not necessary to remove the eggshell membrane from the raw eggshells in order to produce industrial-grade CaO from the raw eggshell. These new findings can likely be used to develop an alternative process design to reduce the manufacturing cost of bio-CaO produced from hatchery waste. Furthermore, this present study reveals that the specifications of the obtained bio-CaO comply with both Thai industrial standards and international food additive standards.